Responses of oak pollards to pruning. Issue 3 (3rd July 2021) - Bengtsson, Vikki; Wheater, C. Philip; Read, Helen; Harris, Reg
ABSTRACT: Pruning techniques, used to conserve lapsed oak pollards, were assessed on 41 trees at Ashtead Common, Surrey. Tree response, between three and seven growing seasons after cutting, was compared with the cutting techniques used. The results provide some indications about the techniques that might maximise the success of working trees with this history of management in Southeast England and furthers our understanding of managing old oak pollards wherever they occur. When restoring lapsed oak pollards, choose trees that have good or high vitality, and that have lots of branches. Leave a few uncut branches when pruning and reduce the proportion of rip cuts used. Leaving stubs on oak does not seem to be as important as on lapsed beech pollards. If possible, cut branches less than 30 cm in diameter and with good epicormic growth. A flow chart is provided to help the decision process.